Fetal anaemia from red blood cell membrane defect and co-inherited haemoglobin Constant Spring. (27th July 2015) - Srisupundit, Kasemsri; Charoenkwan, Pimlak; Traisrisilp, Kuntharee; Tongsong, Theera
Abstract : The case presented here is an example of hereditary red blood cell membrane defect with a co-inherited haemoglobin Constant Spring. This case is of an anaemic fetus that presented with isolated ascites at 18 weeks of gestation. Fetal blood analysis revealed abnormal shaped red blood cells. The same pattern of red blood cell morphology was also seen on paternal peripheral blood smear. Intrauterine blood transfusions were given twice to correct fetal anaemia. The fetus showed a good response to the transfusions and was delivered at term with mild anaemia and did not need blood transfusion after birth. This report describes a natural course of red blood cell membrane defect with co-inherited haemoglobin Constant Spring, indicating that the course of disease was more severe during fetal life. Intrauterine transfusion supported the transition of the fetus through the critical period in utero to a healthier life after birth.